Proceedings of the Thirty-Second International Joint Conference on Artificial Intelligence 2023
DOI: 10.24963/ijcai.2023/665
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Underlying Meaning of Multimodal Hateful Memes

Abstract: Recent studies have proposed models that yielded promising performance for the hateful meme classification task. Nevertheless, these proposed models do not generate interpretable explanations that uncover the underlying meaning and support the classification output. A major reason for the lack of explainable hateful meme methods is the absence of a hateful meme dataset that contains ground truth explanations for benchmarking or training. Intuitively, having such explanations can educate and assist content mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…While we did not explore this in greater detail, there is likely substantial variation within these two categories as well. Memes could be political in nature, or be about relationships, work/school, or hateful (Hee et al, 2023). In other words, even though a clustering of social media content into genres and topics is possible, our research illustrates that passive SMU is characterized by truly significant levels of content heterogeneity.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…While we did not explore this in greater detail, there is likely substantial variation within these two categories as well. Memes could be political in nature, or be about relationships, work/school, or hateful (Hee et al, 2023). In other words, even though a clustering of social media content into genres and topics is possible, our research illustrates that passive SMU is characterized by truly significant levels of content heterogeneity.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies on categorization of memes have generally found low or even lower inter-rater agreement scores (seeChen et al, 2023;Hee et al, 2023).…”
mentioning
confidence: 98%
“…Meme Comprehension: Given a meme image I and the meme texts C, meme comprehension requires to decode the meaning of multimodal memes. For instance, the meme in Figure 3 To supervise the learning of modules, we use the annotated interpretation of hateful memes in [13] as training data.…”
Section: Relevantmentioning
confidence: 99%